Analysis of Existing and Forecasting for Coal and Solar Energy Consumption on Climate Change in Asia Pacific: New Evidence for Sustainable Development Goals - Kurniadi, Anggi Putri; Aimon, Hasdi; Salim, Zamroni; Ragimun, Ragimun; Sonjaya, Adang; Setiawan, Sigit; Siagian, Viktor; Nasution, Lokot Zein; Nurhidajat, R; Mutaqin, Mutaqin; Sabtohadi, Joko (International Journal of Energy Economics and Policy, 2024)
This study aims to identify trends in the role of coal and solar energy consumption on climate change through existing and forecasting analysis as new evidence for the sustainable development goals launched by 2030. This research targets countries in the Asia Pacific, especially coal exporters (Indonesia and Australia) and coal importers (China). The basic model uses panel regression as the existing condition, which covers the period 2008-2023. Meanwhile, the forecasting analysis uses the ARIMA method, which covers the period 2024-2030. The findings of existing conditions include coal energy consumption contributing to increasing climate change. Meanwhile, solar energy consumption can reduce climate change. Furthermore, the forecast findings on average are climate change conditions of 5.237 million tons and coal energy consumption of 33,830 exajoules, but on average the annual growth rate is relatively small (0.91 percent for climate change and 1.46 percent for coal energy consumption). Meanwhile, solar energy has also increased with a small quantity of 2.40 exajoules, but the growth rate is relatively high (29.61 percent). This research recommends that the government massively increase the transition of clean energy consumption towards solar so that the mix can dominate for greater reductions in climate change in achieving sustainable development goals.